On the origins of cognitive science : the mechanization of the mind - Dupuy, Jean-Pierre, 1941- (Cambridge, Mass. : MIT Press, 2009)
The self-mechanized mind -- The fascination with models -- A poorly loved parent -- The limits in interdisciplinarity -- Philosophy and cognition -- From information to complexity -- Aspects of a failure.
Originally published: Princeton : Princeton University Press, 2000.
boek